2015
DOI: 10.1016/j.jvoice.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Evaluation of Dysphonic Voices: Can a Training Protocol Lead to the Development of Perceptual Categories?

Abstract: The purpose of this study was to develop and test a training protocol for the perceptual evaluation of dysphonia. A group of 38 inexperienced listeners participated in a three-phase experiment: a pretest to evaluate their initial performance on categorization of dysphonic voices, a training phase, and a posttest to detect training-related changes in performance. In parallel, a different group of 14 listeners who were experts in voice assessment took a test that was identical to the posttest taken by the inexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
2
10
0
6
Order By: Relevance
“…The controversy also concerns the impact of speech task on the interrater reliability since some authors did not find significant differences in interrater reliability between dysphonia severity ratings of sustained vowels and continuous speech [13, 20, 21], while others supported that the counting task and/or sustained /a/ phonation are the optimal tasks for perceptual voice judgment with regard to interrater reliability [17]. Most of the studies selected perceptual moderate or severe dysphonia samples to demonstrate a task’s effect, but they did not compare the absolute agreement, intra- and interrater reliabilities of mild or moderate dysphonia that often remain harder to grade than severe dysphonic voice [22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…The controversy also concerns the impact of speech task on the interrater reliability since some authors did not find significant differences in interrater reliability between dysphonia severity ratings of sustained vowels and continuous speech [13, 20, 21], while others supported that the counting task and/or sustained /a/ phonation are the optimal tasks for perceptual voice judgment with regard to interrater reliability [17]. Most of the studies selected perceptual moderate or severe dysphonia samples to demonstrate a task’s effect, but they did not compare the absolute agreement, intra- and interrater reliabilities of mild or moderate dysphonia that often remain harder to grade than severe dysphonic voice [22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…Research studies on vocal perceptual evaluations looked further into why perceptual ratings were less reliable and what could be done to improve them. These studies found that reliability was better for the least and most severe voice samples (Ghio et al, 2014;Kreiman, Gerratt, & Ito, 2007), listener experience influenced reliability (De Bodt, 1997;Ghio et al, 2014;Karnell et al, 2007;Kreiman, Gerratt, & Precoda, 1990;Sofranko & Prosek, 2014) and training programs for naïve listeners were effective in improving reliability (Awan & Lawson, 2009;Chan & Yiu, 2006;Eadie & Baylor, 2006;Ghio et al, 2014;Iwarsson & Reinholt Petersen, 2012;Yamaguchi, Shrivastav, Andrews, & Niimi, 2003).…”
Section: List Of Figuresmentioning
confidence: 99%
“…This makes it challenging for students to become proficient and reliable in evaluating voices. Even the reliability of judgments made by experienced raters is often variable; however, perceptual training programs for experienced and inexperienced raters have reduced intra-and inter-rater variability (Chan & Yiu, 2002;Eadie & Baylor, 2006;Ghio et al, 2014;Yamaguchi et al, 2003). Some training literature and practices in speech-language pathology suggested that imitation of disordered speech or voice quality can be useful for developing perceptual judgment skills (DeBoer & Shealy, 1995;Duffy, 2013), but this premise has not been evaluated by the research literature on perceptual voice evaluations.…”
Section: List Of Figuresmentioning
confidence: 99%
See 2 more Smart Citations